Prognostic Role of S100A8 in Human Solid Cancers: A Systematic Review and Validation - Huang, An; Fan, Wei; Liu, Jiacui; Huang, Ben; Cheng, Qingyuan; Wang, Ping; Duan, Yiping; Ma, Tiantian; Chen, Liangyue; Wang, Yanping; Yu, Mingxia (Frontiers in Oncology, 2020)
Background: S100A8 plays a key role in many cellular processes and is highly expressed in various solid cancers. However, the prognostic role of S100A8 has not been well defined. Therefore, we conducted a quantitative meta-analysis to investigate whether or not S100A8 could be used as a prognostic biomarker in solid tumors. Methods: PubMed, Web of Science, Embase, and Cochrane library were searched to acquire relevant studies that evaluated the association between expression of S100A8 and prognosis of cancer patients. Pooled hazard ratios (HRs) with their corresponding 95% confidence intervals (CIs) were extracted to evaluate the association between S100A8 overexpression and Overall Survival (OS), Disease-Free Survival (DFS), Recurrence-Free Survival (RFS) and Progression-Free Survival (PFS). The expression of S100A8 was also validated by Flow cytometry, immunohistochemistry (IHC) and western blot. Results: A total of 2,817 patients from 13 independent studies, ranging from 43 to 1117 patients in size, were statistically analyzed. Our results indicated that a high level of S100A8 expression was significantly associated with poor OS, poor DFS, and poor PFS/RFS. In term of clinical pathological characteristics, a high expression level of S100A8 was significantly associated with differentiation grades, lymphatic metastasis, ER statue, and PR statue. The validation studies showed that the expression of S100A8 was at high levels in MDA-MB-231 (79.7%), MDA-MB-453 cells (89.2%), HTB-9 (70.2%), and T24 (53.3%) and it was higher in breast cancer tissue and bladder cancer tissue than their corresponding para-carcinoma tissue. Conclusions: S100A8 overexpression was significantly associated with poor clinical prognosis in cancer patients. S100A8 is potential a prognostic biomarker in breast cancer and bladder cancer. More well-designed studies with adequate prognostic data are needed to confirm the prognostic role of S100A8 revealed in this study.